Navigating Success: The Impact of Social Media Strategies on Small and Medium-Scale Businesses in Ikot Ekpene, Akwa Ibom State, Nigeria - Aniediabasi James Udom; Joshua Christopher Ekpouko (International Journal of Innovation in Marketing Elements)
Purpose: The increasing influence of social media has significantly transformed small and medium scale businesses (SMSBs) operations in developing regions. This study assesses the impact of various social media tools on SMSB performance in Ikot Ekpene Local Government Area, Akwa Ibom State, Nigeria. It aims to evaluate the effectiveness of tools such as content creation, marketing strategies, brand building, networking, and e-commerce integration. Methodology: Using a survey design, data were collected from 331 respondents out of a sample of 363 SMSBs, drawn from a population of approximately 3,957, determined using the Yaro Yamane formula. Structured questionnaires facilitated data collection, and analyses included simple percentages, frequency tables, SPSS coding, and multiple regression analysis.